Knowledge mapping and research trends of exosomes in pancreatic cancer: a bibliometric analysis and review (2013-2023) - Zhou, Yongjiang; Feng, Jiajie; Wang, Qingqing; Zhao, Yiwen; Ding, Hanyu; Jiang, Kexin; Ji, Hua; Tang, Zheng; Dai, Ruiwu (Frontiers in Oncology, 2024)
Objective: This review aims to provide a quantitative and qualitative bibliometric analysis of literature from 2013 to 2023 on the role of exosomes in PC, with the goal of identifying current trends and predicting future hotspots.Methods: We retrieved relevant publications concerning exosomes in PC, published between 2013 and 2023, from the Web of Science Core Collection. Bibliometric analyses were conducted using VOSviewer(1.6.19), CiteSpace(6.2.R4), and Microsoft Excel(2019).Results: A total of 624 papers were analyzed, authored by 4017 researchers from 55 countries/regions and 855 institutions, published in 258 academic journals. China (n=285, 34.42%) and the United States (n=183, 24.87%) were the most frequent contributors and collaborated closely. However, publications from China had a relatively low average number of citations (41.45 times per paper).The output of Shanghai Jiao Tong University ranked first, with 28 papers (accounting for 4.5% of the total publications). Cancers (n=31, 4.9%;) published the most papers in this field. Researcher Margot Zoeller published the most papers (n=12) on this topic. Research hotspots mainly focused on the mechanisms of exosomes in PC onset and progression, the role of exosomes in PC early diagnosis and prognosis, exosomes promote the development of PC chemoresistance, and potential applications of exosomes as drug carriers for PC therapies. We observed a shift in research trends, from mechanistic studies toward clinical trials, suggesting that clinical applications will be the focus of future attention. Emerging topics were pancreatic stellate cells, diagnostic biomarkers, mesenchymal stem cells, extracellular vesicles. Conclusion: Our scientometric and visual analysis provides a comprehensive overview of the literature on the role of exosomes in PC published during 2013 -2023. This review identifies the frontiers and future directions in this area over the past decade, and is expected to provide a useful reference for researchers in this field.